Sialometric and Sialochemical Analysis in Individuals With Pulp Stones - Gabardo, Marilisa Carneiro Leão; Kublitski, Prescila Mota de Oliveira; Sette, Isabela Rodrigues; Lauschner, Thaís; Juglair, Mariana Martins; Baratto-Filho, Flares; Brancher, João Armando; Michel-Crosato, Edgard (Frontiers in Cell and Developmental Biology, 2020)
The aim of this study was to analyze the saliva of patients with pulp stones, with sialometric and sialochemical tests. Eighty individuals, aged between18 to 65 years, of both sexes, were investigated. Patients were included in the pulp stone group when radiographic examination was suggestive of pulp stones in at least one permanent tooth, whereas those without this alteration were considered controls. Saliva was collected by stimulation, followed by salivary flow rate (SFR) and pH analysis’ tests. The organic components: urea, glucose, total proteins, alkaline phosphatase, creatinine, salivary amylase, and uric acid; and the inorganic components: calcium, iron, and phosphorus were evaluated by colorimetric techniques in an ultraviolet-visible spectrophotometer. Differences among pulp stones and control groups were compared using Student’s t-test, with a significance level of p <0.05. In both groups prevailed the females. Statistically significant differences between groups were observed for pH (p = 0.027), SFR (p = 0.002), alkaline phosphatase (p = 0.008), and uric acid (p = 0.005). None of the inorganic components showed significant difference (p > 0.05). In the analyses stratified by sex, difference between groups was observed for pH (p = 0.007) and uric acid (p = 0.003) in women. In conclusion, sialometric and sialochemical alterations occurred in patients with pulp stones, with significantly higher levels of pH, SFR, alkaline phosphatase, and uric acid.